Unveiling Physical Conditions and Star Formation Processes in the G47 Filamentary Cloud - O. R. Jadhav; L. K. Dewangan; A. Haj Ismail; N. K. Bhadari; A. K. Maity; Ram Kesh Yadav; Moustafa Salouci; Patricio Sanhueza; Saurabh Sharma (The Astrophysical Journal)
We present a multiwavelength study of the filamentary cloud G47 ( d ∼ 4.44 kpc), which hosts the mid-infrared bubbles N98, B1, and B2. The SMGPS 1.3 GHz continuum map detects ionized emission toward all the bubbles, marking the first detection of ionized emission toward the B2 bubble. Analysis of the unWISE 12.0 μ m image, the Spitzer 8.0 μ m image, and the Herschel column density and temperature maps reveals two previously unreported hub–filament system candidates associated with the H ii regions B2 and N98, which are powered by massive OB stars. This indirectly favors the applicability of a global nonisotropic collapse scenario for massive star formation in N98 and B2. The position–position–velocity diagram of FUGIN ^13 CO (1–0) shows significant velocity variations from 61 to 53 km s ^−1 toward areas between B2 and N98, where the magnetic field morphology exhibits significant curvature and high velocity dispersion (i.e., 2.3–3.1 km s ^−1 ) is observed. This may be explained by the expansion of the H ii regions B2 and N98. The energy budget of the cloud, estimated using SOFIA/HAWC+ and molecular line data, suggests that the magnetic field dominates over turbulence and gravity in G47. Furthermore, the radial column density and velocity profiles of G47 display signatures of converging flows in a sheet-like structure. The relative orientations between the magnetic field and local gravity suggest that G47 may undergo gravitational contraction along the magnetic field lines once it becomes magnetically supercritical.